2009
DOI: 10.1111/j.1471-0528.2009.02364.x
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid interleukin‐18 at mid‐trimester genetic amniocentesis: relationship to intraamniotic microbial invasion and preterm delivery

Abstract: Objective To determine the value of amniotic fluid interleukin-18 (AF IL-18) in the diagnosis of microbial invasion of the amniotic cavity and prediction of preterm delivery (PTD). Setting A tertiary referral centre for fetal medicine.Methods Following amniocentesis, a sample of amniotic fluid was transferred to the laboratory for aerobic and anaerobic bacterial cultures, Ureaplasma urealyticum culture and IL-18 assays. All women who delivered preterm (<37 weeks of gestation) formed the study group. The contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…For the fetus or neonate, infections with Ureaplasma are associated with a number of adverse outcomes, including chronic lung disease, pneumonias, cerebral white matter lesions, cerebral palsy and even death [4]; [5]. The mechanisms by which Ureaplasmas cause such diseases remain unclear, but it is believed that inappropriate induction of inflammatory responses is involved, most likely triggered by the innate immune system [6]; [7]. It is believed that the innate immune response to these bacteria can lead to the activation of pattern recognition receptors (PRRs), production and release of pro-inflammatory mediators leading to the complications associated with preterm and term infants.…”
Section: Introductionmentioning
confidence: 99%
“…For the fetus or neonate, infections with Ureaplasma are associated with a number of adverse outcomes, including chronic lung disease, pneumonias, cerebral white matter lesions, cerebral palsy and even death [4]; [5]. The mechanisms by which Ureaplasmas cause such diseases remain unclear, but it is believed that inappropriate induction of inflammatory responses is involved, most likely triggered by the innate immune system [6]; [7]. It is believed that the innate immune response to these bacteria can lead to the activation of pattern recognition receptors (PRRs), production and release of pro-inflammatory mediators leading to the complications associated with preterm and term infants.…”
Section: Introductionmentioning
confidence: 99%
“…Functionally, both variants were linked with reduced IL-18 availability, evidenced by a progressive reduction in serum IL-18 levels in heterozygous and homozygous carriers in both patients and control women. These findings underscore the significance of reduced IL-18 levels in the maintenance of normal pregnancy (12,21), and in the pathogenesis of pregnancy complications (6,8,28), including RSM (21).…”
Section: Discussionmentioning
confidence: 72%
“…IL-18 promotes inflammation indirectly by stimulating IL-1b expression, which by structurally resembling IL-18, binds IL-18 receptors and thus potentiates proinflammation (2, 3) by engaging similar signaling and signal transduction (2,4). Alterations of IL-18 have been investigated in the susceptibility to autoimmune and inflammatory disorders (4,5), and changes in IL-18 levels have been linked with pregnancy complications, including preeclampsia (6,7), preterm delivery (8), IVF-ET failure (9), implantation failure (4,10), and recurrent miscarriage (10)(11)(12).…”
mentioning
confidence: 99%
“…Subsequently, several casecontrol studies have demonstrated an association between the amniotic fluid IL-6 concentration at the time of mid-trimester amniocentesis and preterm delivery [186, 191, 193]. The same has been reported for other cytokines [4, 20, 30, 102, 103, 139, 140, 186, 210]. A limitation of case control studies is that they are prone to biases.…”
Section: Introductionmentioning
confidence: 92%